Psychosocial Health of the Badjao People During COVID-19 in Jolo, Philippines: An Exploratory Study - Masong, Zhendra T.; Pangandaman, Hamdoni K. (Nurse Media Journal of Nursing, 2024)
Background: The Badjao, a nomadic maritime group in Southeast Asia, faces heightened vulnerability during public health crises due to their reliance on maritime livelihoods, limited healthcare access, and historical marginalization – challenges exacerbated by the COVID-19 pandemic. However, there is a significant research gap in understanding their unique needs and vulnerabilities, especially its specific impacts on their health and well-being due to the pandemic.Purpose: This study explores the psychological and social health of the Badjao and the factors affecting them during the COVID-19 pandemic.Methods: This study used an exploratory qualitative design. Guided semi-structured interviews were conducted with 10 purposively selected Badjao respondents from Barangay Bus-Bus, Jolo-Sulu, Philippines. The data were analyzed using thematic analysis.Results: The study identified five key themes related to the psychosocial health of the Badjao community during COVID-19 and the affecting factors. They were: (1) Feelings and apprehension, with anxiety over contracting the virus and financial instability; (2) Responses to the pandemic, marked by fear of death, job loss, and hospitalization concerns; (3) Coping mechanisms, where the community relied on traditional remedies, social support, and quarantine adherence; (4) Social status, highlighting food insecurity and disrupted social interactions; and (5) Factors influencing psychosocial health, focusing on the importance of support systems and access to accurate information and resources.Conclusion: The COVID-19 pandemic has significantly disrupted the social and economic stability of the Badjao community, exacerbating their existing vulnerabilities. The community needed culturally sensitive interventions that addressed both their immediate and long-term needs. Collaborations with local government units and stakeholders are crucial in supporting the resilience and well-being of the Badjao in future crises.